Australia : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper for Australia highlights the dynamics of the Australian real exchange rate and its impact on Australia's trade. The main findings are that the Australian real exchange rate is largely driven by world commodity prices and that it adjusts relatively rapidly to large shocks, with an estimated half-life of 16 months. The real exchange rate is a significant determinant of Australian imports, with an elasticity of one, but does not appear to have a significant impact on Australian exports.